Civil society the international: a global power? (2007)
This article aims at sinthetizing different perspectives about the rol of internacional civil society (ICV) in the exercise of a global power. It refers to some anglosajon and european recent studies, both at theorical as empirical levels, in order to do an evaluation of the most critical results. Being esceptical about the very concept of ICV, it tries to analize it from different points of view, in order to respond the main problem: is it posible for the ICV to ejercize power at a global level, and which is its legitimity to resolve global issues. The analysis of the concept is based on some results of the classical theory of civil society at a national level, but also examines specific dificulties to define an ICV and its functions in a globalized world. Eventually, it presents some theoretical challenges which are linked with the relation between ICV and a global democratic order.